Identification and Characterization of a Cryptic Genomic Deletion-Insertion in EYA1 Associated with Branchio-Otic Syndrome - Hao Zheng; Jun Xu; Yu Wang; Yun Lin; Qingqiang Hu; Xing Li; Jiusheng Chu; Changling Sun; Yongchuan Chai; Xiuhong Pang (Neural Plasticity)
Branchio-oto-renal spectrum disorder (BORSD) is characterized by hearing loss accompanied by ear malformations, branchial cysts, and fistulae, with (branchio-oto-renal syndrome (BORS)) or without renal abnormalities (BOS (branchio-otic syndrome)). As the most common causative gene for BORSD, dominant mutations in EYA1 are responsible for approximately 40% of the cases. In a sporadic deaf patient diagnosed as BOS, we identified an apparent heterozygous genomic deletion spanning the first four coding exons and one 5′ noncoding exon of EYA1 by targeted next-generation sequencing of 406 known deafness genes. Real-time PCR at multiple regions of EYA1 confirmed the existence of this genomic deletion and extended its 5′ boundary beyond the 5′-UTR. Whole genome sequencing subsequently located the 5′ and 3′ breakpoints to 19268 bp upstream to the ATG initiation codon and 3180 bp downstream to exon 5. PCR amplification across the breakpoints in both the patient and his parents showed that the genomic alteration occurred de novo. Sanger sequencing of this PCR product revealed that it is in fact a GRCh38/hg38:chr8:g.71318554_71374171delinsTGCC genomic deletion-insertion. Our results showed that the genomic variant is responsible for the hearing loss associated with BOS and provided an example for deciphering such cryptic genomic alterations following pipelines of comprehensive exome/genome sequencing and designed verification.